The Effect of E-Service of Quality on Customer Satisfaction in Using The Shopee Application - Hartati, Wiwi; Desy Lusiyana, Desy; Nurmelia, Rizcita (International Journal of Advanced Multidisciplinary, 2023)
This research was conducted by distributing questionnaires for data collection. This questionnaire was distributed to Management Study Program Students of the University of Muhammadiyah Cirebon who used the shopee application. And obtained a sample of 40 students who had filled out the questionnaire. This research uses quantitative methods because the data obtained is statistical to test certain hypotheses. Based on the theoretical foundation and frame of mind above, this study hypothesizes that E-Service Quality affects Customer Satisfaction. The result of this experiment is E-Service Quality is included in the good category. This means that the e-service quality owned in the shopee application is in good condition. Customer Satisfaction in the shopee application is good. Based on the results of data processing, it has been concluded that e-service quality affects customer satisfaction in the shopee application. This shows that the better the e-service quality of the shopee application, the higher the customer satisfaction will also be in the shopee application.